Add Female Veterans and Stir? A Feminist Perspective on Gendering Veterans Research. (October 2017) - Eichler, Maya
This article examines how scholarship on veterans has begun to incorporate gender as a relevant category of research. Drawing on feminist theory, it identifies different approaches to gender within the field of veterans studies and suggests avenues for advancing this aspect of research. The vast majority of gender research on veterans treats gender as a descriptive category or variable through a focus on female veterans or gender differences. This article argues that research on veterans can be enriched by employing gender as an analytical category. Focusing on gender norms, power and inequality based on gender, and the intersections of gender with other categories of social difference opens up new questions for gender research on veterans. This kind of broader, analytical conceptualization of gender reveals the ways in which gender shapes the transition to civilian life for all veterans and how veterans policies and programs impact gender relations.